CMOS-based current-mode tunable ladder Elliptic low-pass filter - Prommee, Pipat; Kunto, Terdsak; Somdunyakanok, Montri; Prommee, Tanakrit (My University, 2015)
This paper presents a tunable CMOS-based third-order low-pass filter that can be operated in high frequency. The proposed low pass filter is designed based on Elliptic Ladder low-pass filter prototype. The proposed filter structure is constructed by using two lossy integrators and a lossless integrator. The proposed filter comprises only 18 transistors. The frequency responses of low-pass filter can be electronically tuned between 10kHz and 100MHz through bias current from 0.01 μA to 100 μA. The circuit used 1.5 V power supply with 3mW power consumption at 100 μA bias current. Using of the grounded capacitors which is suitable for further integration. THD of low-pass filter can be obtained less than 1% along the operating frequencies. PSPICE simulation results are carried out to confirm the theory by using TSMC 0.18μm technology.
Keywords: CMOS; Elliptic; High frequency; Ladder; low-pass